2013
DOI: 10.1002/anie.201306774
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Bromocyclization of Tryptamines and Its Application in the Synthesis of (−)‐Chimonanthine

Abstract: A shorter path: A highly enantioselective bromocyclization of tryptamine has been developed using an anionic chiral phase-transfer catalyst. This method provides a direct approach for preparing chiral 3-bromopyrroloindoline from tryptamine, which enables a four-step enantioselective synthesis of (-)-chimonanthine. PG=protecting group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(69 citation statements)
references
References 63 publications
2
64
0
3
Order By: Relevance
“…48 Later work by the same authors on a closely related bromocyclization found that mixtures of “monocationic” and “tricationic” DABCO-derived “Br + ” salts closely related to 22 and 19 gives optimal performance. 49 …”
Section: Challenges For Stereoselective Catalysismentioning
confidence: 99%
“…48 Later work by the same authors on a closely related bromocyclization found that mixtures of “monocationic” and “tricationic” DABCO-derived “Br + ” salts closely related to 22 and 19 gives optimal performance. 49 …”
Section: Challenges For Stereoselective Catalysismentioning
confidence: 99%
“…Displacement of C3a-bromo pyrroloindolines can be achieved with the use of stoichiometric base, but these reactions typically only function well when an ester is present at C2. 10 Otherwise silver salts are often utilized, 11 but these conditions often require the use of superstoichiometric amounts of these expensive reagents. Single electron transfer conditions have also been explored for substitution of the bromide with carbon nucleophiles.…”
mentioning
confidence: 99%
“…[4][5][6] Recently, asymmetric anionic phase-transfer reactions 7,8) have been reported using chiral phosphates with an aziridinium cation 9) and N-haloammonium cations. [10][11][12][13][14][15][16][17][18] …”
mentioning
confidence: 99%